IMPLEMENTASI PENDIDIKAN ISLAM BERBASIS INTEGRASI ILMU AGAMA, SAINS DAN TEKNOLOGI PADA MAN INSAN CENDEKIA - Muhlisin Muhlisin; Mohammad Syaifuddin (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
Islamic educational institutions are encouraged to implement the model of integrated Islamic education in recent years. They are supposed to integrate Islamic studies, science and technology. The present study aims to reveal the reasons why MAN IC Pekalongan implement an integrated Islamic education model, describe the implementation of students’ activities programs based on science integration, describe the implementation of curriculum development based on science integration, describe the learning implementation based on the integration of Islamic studies, science and technology. Grounded in qualitative approach, data were garnered through interview, observation, and documentation. Data were analyzed through reduction, display, and data verification. The study findings expose that: first, the reasons of integrating Islamic studies, science and technology is to reach the vision of the school which aims to be excellent both on academic and non-academic areas which then be able to improve the quality of madrasah as an integrative Islamic education institution. Second, the students’ activity program used is the model of Separated Integration System (SIS). Third, the curriculum development program used is the model of Integrated Tree Curriculum (ITC). Fourth, the learning implementation uses the model of Integrating Verb (IV), Interdisciplinary Dialogic Integration (IDI), Instrumentalist Justification Integration (IJI), and reflective technique.